Engaging electrical lighting installation classes: Android interactive learning media development with Adobe Animate CC - Nuraminah, Nuraminah; Azim, Fauzan; Anshari, Khairul; Urazaliyeva, Ulzhan (Journal of Computer-based Instructional Media, 2024)
This study aims to develop android-based interactive learning media for Electrical Lighting Installation subjects by using Adobe Animate CC. The research was conducted in response to the limited variation of learning media, which has affected student engagement and motivation in technical subjects. The Research and Development (R&D) model, adapting a 3D out of 4D model (Define, Design, Develop) was referred to develop interactive media designed for vocational students. The media integrates audiovisual elements to enhance students' learning experiences and promote independent learning outside the classroom. The validation process utilized questionnaires, interviews, and observations from content experts, media experts, and students. The media was validated by experts in two stages. In the first stage, the media achieved a feasibility score of 68%, categorized as "fairly good." After revisions, the second validation showed an improvement with a feasibility score of 85.33%, categorized as "very good". The results indicate that the Android-based learning media potentially enhance the learning process of Electrical Lighting Installation subjects effectively, providing a more engaging and flexible tool for students. This innovation significantly contributes to improving the quality of technical education by offering an accessible and interactive learning resource. It also addresses the challenges of limited learning media variation and encourages independent learning, possibly serving as a model for the development of similar media in other technical subjects.